Who«s your city? : how the creative economy is making where to live the most important decision of your life - Florida, Richard L. (Basic Books, Inc, 2008)
Economics/Current Events Hardcover - Which college to attend? What career to pursue? Whom to marry? Important choices all, but none as vital as the most critical decision you'll ever make: where to live. Based on more than twenty years of research. Shows how a new economic unit-the mega-region-is the real driver of the global economy. Where we choose to live is increasingly a crucial decision in our lives, and Who's Your City? is the indispensable guide to making that decision intelligently.